IL4I1 is a metabolic immune checkpoint that activates the AHR and promotes tumor progression - Sadik, Ahmed; Somarribas Patterson, Luis F.; Öztürk, Selcen; Mohapatra, Soumya R.; Panitz, Verena; Secker, Philipp F.; Holfelder, Pauline; Loth, Stefanie; Salem, Heba; Prentzell, Mirja Tamara; Berdel, Bianca; Iskar, Murat; et al. (Cell, 2020)
Aryl hydrocarbon receptor (AHR) activation by tryptophan (Trp) catabolites enhances tumor malignancy and suppresses anti-tumor immunity. The context specificity of AHR target genes has so far impeded systematic investigation of AHR activity and its upstream enzymes across human cancers. A pan-tissue AHR signature, derived by natural language processing, revealed that across 32 tumor entities, interleukin-4-induced-1 (IL4I1) associates more frequently with AHR activity than IDO1 or TDO2, hitherto recognized as the main Trp-catabolic enzymes. IL4I1 activates the AHR through the generation of indole metabolites and kynurenic acid. It associates with reduced survival in glioma patients, promotes cancer cell motility, and suppresses adaptive immunity, thereby enhancing the progression of chronic lymphocytic leukemia (CLL) in mice. Immune checkpoint blockade (ICB) induces IDO1 and IL4I1. As IDO1 inhibitors do not block IL4I1, IL4I1 may explain the failure of clinical studies combining ICB with IDO1 inhibition. Taken together, IL4I1 blockade opens new avenues for cancer therapy.